Driving giants: spatial and temporal variables influencing giraffe movements in a private protected area - Allouchery, Zoe (Department of Biological Sciences, 2024)
Spatiotemporal factors play important roles in shaping interactions between species within ecosystems, influencing their behavior and survival strategies. For predator/prey interactions, survival of the prey may rely heavily on spatial and temporal characteristics of the landscape together with species-specific behavioral strategies. The fear of predation prompts antipredator responses in prey which include vigilance behavior, grouping, and shifts in habitat selection. However, these responses may incur costs, impacting energy expenditure of prey and time allocation of prey activities such as foraging, sleeping, drinking, and fleeing predators. This study investigates spatiotemporal habitat use characteristics of southern giraffes (Giraffa giraffa) and lions (Panthera leo) within a small private protected area in South Africa where lions are the primary predator of giraffes. Giraffes are most vulnerable to predation when young, sick, or when in a splay-legged position while drinking water. In addition to direct predation risk, the presence of lions in the landscape may influence a ‘landscape of fear', triggering general antipredator behaviors. Giraffe movement and landscape use within the reserve may therefore be strongly influenced by the presence of lions, together with various environmental factors such as water accessibility, habitat preferences, and the need for sufficient food intake to meet their substantial daily energy requirements. This study uses GPS collar data collected over two years from simultaneously collared lions and giraffes in a private game reserve in South Africa's North West Province, the !Khamab Kalahari Nature Reserve. Using this data, t-LoCoH home ranges were calculated to identify patterns of seasonal change and overlap between lions and giraffes. Resource selection function models (RSFs) were then used to identify spatiotemporal variables that influence giraffe movement in a landscape with lions. Variables were resource proximity, including distance to waterholes, NDVI, land cover, landforms, a predation risk variable, and a temporal variables, seasonality and time of day. There was high overlap between all lion and giraffe home ranges (73.9 to 92.2%), suggesting a high probability of encounters between the two species in the reserve. RSFs revealed season, time of day, proximity to waterholes, NDVI, and land cover were significant predictors of giraffehabitat and resources use. Importantly, ‘distance to the closest lion' was also included as a significant variable in the best-fit model. The findings suggest that, within this reserve, giraffes select for areas of higher NDVI and those closer to waterholes. Their presence in the landscape also suggests some avoidance of lions, preferring sites further from lions. In terms of land cover, giraffes selected areas with woodland and transformed land despite their lower proportion on the reserve. Grasslands, the most abundant land cover type, exhibited neither preference nor aversion. Overall, this study identified four spatial variables and two temporal variables that influence giraffe movement within this fenced, semi-arid, small reserve. The insights gained are valuable for understanding how predators impact prey species in managed game reserves, where natural ecological processes may be disrupted to varying degrees and necessitate careful management. Furthermore, given the significance of giraffes as tourist attractions, understanding their ecological requirements is crucial for both their welfare and effective reserve management.